Low-risk innovative ideas with high self-confidence: innovation process characteristics in ASEAN countries - Furue, Nanami; Abdul Aziz, Yuhanis; Mori, Koichiro; Hermawan, Ancella Anitawati; Assarut, Nuttapol; Uehara, Wataru; Washida, Yuichi (World Scientific Publishing, 2020)
To understand the characteristics of ASEAN countries that are conducive to unique innovation, a series of idea generation and selection experiments were conducted in three emerging countries, Malaysia, Indonesia, and Thailand, which were compared with one developed country, Japan. The experiments consisted of one-day-workshops held in each of the four countries. Two significant differences were found between emerging and developed countries. First, participants from the ASEAN countries proposed ideas that entailed a lower investment risk than did the Japanese participants. Secondly, the ASEAN participants were more confident in their idea selection than the Japanese participants were. The results suggested new possibilities for the development of strategies encouraging collaboration between emerging and developed countries in innovation management.